Efficient Semi-Analytic Technique for Solving Nonlinear Singular Initial Value Problems - Tawfiq, Luma N. M.; Hussein, Reem W. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The aim of this paper is to present a semi - analytic technique for solving singular initial value problems of ordinary differential equations with a singularity of different kinds to construct polynomial solution using two point osculatory interpolation. The efficiency and accuracy of suggested method is assessed by comparisons with exact and other approximate solutions for a wide classes of non–homogeneous, non–linear singular initial value problems. A new, efficient estimate of the global error is used for adaptive mesh selection. Also, analyze some of the numerical aspects relevant for the implementation, describe measures to increase the efficiency of the code and compare its performance with the performance of established standard codes for singular initial value problems. Many examples are presented to demonstrate the applicability and efficiency of the suggested method on one hand and to confirm the convergence order on the other hand.